Influência do estágio de regeneração da vegetação nativa e do uso agrícola do solo na diversidade, homogeneização biótica e ecologia de lagartos em áreas do domínio caatinga - Melo, Ana Carolina Brasileiro (2022)
Anthropogenic alterations in the habitat are one of the main threats to biodiversity. Understanding how species diversity and their functions are affected by anthropic changes is crucial to assess the action of environmental impacts, in addition to contributing to decisionmaking aimed at protecting the environment. In this work, we evaluated how taxonomic and functional diversity in lizard (Squamata) assemblages, as well as aspects of their ecology, respond to changes in the stage of native vegetation regeneration and in land use for agriculture. In Chapter I, we present how taxonomic (richness, evenness and abundance) and functional (functional richness, functional evenness and functional divergence) metrics respond to these changes in different types of vegetation in the Caatinga domain (Caatinga sensu stricto, Cerrado sensu stricto and Relictual Humid Forest). We used areas of preserved vegetation (located within conservation units) as a control and compared it to the other stages of vegetation regeneration (closed secondary vegetation and open secondary vegetation) and with the use for agriculture. There was a reduction in evenness and an increase in abundance in all types of vegetation, and a reduction in functional evenness in Caatinga sensu stricto, mainly in areas of agriculture and earlier stages of vegetation regeneration (open secondary vegetation). Thus, the assemblages in these categories were dominated by a smaller number of species and had an increased abundance of tolerant species. Richness increased in areas of agriculture in the Relictual Humid Forest associated with the loss of forest species and colonization by heliophilous species, suggesting that a separate analysis of richness alone may not be sufficient to clearly understand the effects of environmental disturbances on this vegetation type. In Chapter II, we assess whether there are changes in richness at different scales (local and regional), in the similarity in species composition, and whether there is taxonomic and functional homogenization at a regional scale, taking into account changes in the stage of regeneration of native vegetation and in the agricultural land use. Although we found changes in species richness on a local scale (reduction in one of the areas of Caatinga sensu stricto and an increase in Relictual Humid Forest in agriculture areas), we did not record changes on a regional scale, which may be associated with the process of biotic homogenization. We identified an increase in taxonomic dissimilarity at the local level in Caatinga sensu stricto areas, in agricultural areas, and in taxonomic and functional dissimilarity in Relictual Humid Forest, even at later levels vegetation regeneration (closed secondary vegetation), indicating changes more intense dissimilarities in this type of vegetation than in the other investigatedtypes. At the regional level, we identified taxonomic homogenization in open secondary vegetation and agricultural areas, but we did not identify functional homogenization. It is possible that these aspects are attributed, for example, to functional redundancy. In Chapter III we evaluated how the generalist lizard Tropidurus hispidus is affected in its abundance, interaction with parasites and microhabitat use with agricultural land use in relation to areas of native vegetation. T. hispidus abundance increased in agricultural areas only in the general analysis (regional scale) and in the Relictual Humid Forest. In the other areas (Caatinga sensu stricto and Cerrado sensu stricto) the species did not increase in abundance, but neither did it decrease. We recorded differences in the abundance and prevalence of heteroxenous (higher in conserved areas) and monoxenous (higher in agricultural areas) helminths. We did not identify clear patterns in the spatial niche amplitude, which demonstrates its versatility in the use of the microhabitat. These works contribute to the expansion of knowledge of ecology and the effects of environmental disturbances on lizard taxa.